2011
DOI: 10.1007/s11222-011-9297-1
|View full text |Cite
|
Sign up to set email alerts
|

On confidence intervals for semiparametric expectile regression

Abstract: In regression scenarios there is a growing demand for information on the conditional distribution of the response beyond the mean. In this scenario quantile regression is an established method of tail analysis. It is well understood in terms of asymptotic properties and estimation quality. Another way to look at the tail of a distribution is via expectiles. They provide a valuable alternative since they come with a combination of preferable attributes. The easy weighted least squares estimation of expectiles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…The clipped slack variables used in the stopping criteria (27) may provide a substantial decrease in duality gap in each iteration of learning algorithm compared to the unclipped slack variables used in (21), and hence the learning algorithm may require less number of iterations. [34] showed that the right hand side of the stopping criteria given in (21) should be replaced by 2λ as in (27), where has the same value for both.…”
Section: Stopping Criteriamentioning
confidence: 99%
“…The clipped slack variables used in the stopping criteria (27) may provide a substantial decrease in duality gap in each iteration of learning algorithm compared to the unclipped slack variables used in (21), and hence the learning algorithm may require less number of iterations. [34] showed that the right hand side of the stopping criteria given in (21) should be replaced by 2λ as in (27), where has the same value for both.…”
Section: Stopping Criteriamentioning
confidence: 99%
“…A package for R, expectreg, is available in Sobotka et al (2013). It can fit the simple LAWS model (Schnabel & Eilers, 2009b) well as the expectile bundle described in this manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…It combined the LAWS (least average weighted squares) algorithm with P-splines in order to estimate expectile curves. Recent applications include Guo and Härdle (2012), Sobotka et al (2013) and Guo et al (2015) or more applicable one in finance by Taylor (2008), where Value at risk (VaR) and Expected shortfall (ES) were estimated using expectiles.…”
Section: A Construction Of Annual Expectile Curvesmentioning
confidence: 99%